2013
DOI: 10.3126/njh.v7i1.8497
|View full text |Cite
|
Sign up to set email alerts
|

A study on major cardiovascular risk factors in Acute Coronary Syndrome (ACS) patient 40 years and below admitted in CCU of Shahid Gangalal National Heart Center.

Abstract: Coronary artery disease (CAD), predominately manifest in older individuals, is a devastating disease precisely because an otherwise healthy person in the prime of life may die or become disabled without warning. When the afflicted individual is under the age of 40, the tragic consequences for family, friends, and occupation are particularly catastrophic and unexpected. Fortunately, the incidence of myocardial infarction (MI) and symptomatic CAD in young adults is low; most studies show that only about 3% of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
5
1
Order By: Relevance
“…5,9 In a study done by Adhikari CM et al in a capital city heart center 70% patients were smokers who were brought for coronary heart disease in age group up to 40 years. 10 Study done in Central Nepal by Koju R et al showed that among the established cardiovascular risk factors, gender, diabetes mellitus and smoking are significantly associated with coronary stenosis among CAD patients which is in contrast to our study. 7 In our study, non-atherosclerotic lesions were seen in almost all cases except in one case where the right coronary artery showed atherosclerotic lesion.…”
Section: An Autopsy Study Of Atherosclerotic Changes In Coronary Arteriescontrasting
confidence: 99%
“…5,9 In a study done by Adhikari CM et al in a capital city heart center 70% patients were smokers who were brought for coronary heart disease in age group up to 40 years. 10 Study done in Central Nepal by Koju R et al showed that among the established cardiovascular risk factors, gender, diabetes mellitus and smoking are significantly associated with coronary stenosis among CAD patients which is in contrast to our study. 7 In our study, non-atherosclerotic lesions were seen in almost all cases except in one case where the right coronary artery showed atherosclerotic lesion.…”
Section: An Autopsy Study Of Atherosclerotic Changes In Coronary Arteriescontrasting
confidence: 99%
“…14 Different studies conducted in different countries showed LAD was most frequently affected followed by RCA and LCX. [12][13][14] similarly in our study, 75% of CAD cases had LAD lesion.…”
Section: Discussionsupporting
confidence: 82%
“…10 The skewed gender distribution (males 81.65% versus females 18.35%) of the study population can be attributed to the gender bias and atypical presentation, which is also a feature in other South Asian studies. [10][11][12] This can be attributed to gender disparity and inequality in tertiary healthcare facility in Nepali society.…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies have also found high rates of tobacco use among young patients who have AMI, with percentages ranging from 70% to >90%. [10][11][12] Smoking is known to cause increased fibrinogen concentrations and platelet aggregability, along with impaired fibrinolytic activity, decreased coronary flow reserve, and increased vasospasm. [13][14][15] Recurrent exposure to cigarettes with subsequent catecholamine surges damage endothelial cells, leading to endothelial dysfunction and injury of the vascular intima.…”
Section: Discussionmentioning
confidence: 99%